Analisis Exchange Market Pressure di Indonesia Periode Setelah Krisis Moneter - Merina Ayuningtyas; Rudi Purwono (MediaTrend, 2020)
Indonesia is one of the countries that handed over its currency to the exchange market, so the rupiah has fluctuated. The purpose of this study is to test and analyze the exchange market pressure in Indonesia period after the monetary crisis. The method used is ARDL with the period of quarter 1 of 2002 up to quarter 4 of 2017. The estimation result shows that USA economic growth, USA PUAB, M2 growth, and domestic credit have a significant effect on EMP in the long term, while EMP lag 1, USA economic growth lag 3, USA PUAB, Indonesian M2 growth, and Indonesian M2 growth lag 2 have a significant effect, and domestic credit to EMP in the short term.